(untitled) (Eurasian Journal of Philology Science and Education, 2025)
The linguistic landscape is one of the most actively developing areas of modern linguistics. The article examines the linguistic landscape as an object of sociolinguistic research and provides an overview of 774 research papers related to the linguistic landscape published in the Scopus database from 2000 to 2023. The theoretical significance of the research is determined from the point of view of systematization of knowledge related to the linguistic landscape and a deeper understanding of the versatility of modern research in this area. A systematic study of the linguistic landscape makes it possible to clarify the boundaries of this area and identify the main trends in its development. This, in turn, contributes to a deeper understanding of the role of language in social and cultural processes. The results of the study show that the number of studies in the field of linguistic landscape has increased significantly in recent years. This trend means that the linguistic landscape has become an important object of study in many regions, becoming increasingly global. Geographical and industry analysis of publications shows that the problem of linguistic landscape is at the junction of many sciences and requires interdisciplinary research. Research conducted in the fields of sociolinguistics, cultural studies, urban studies and education clearly shows how wide and relevant this problem is. The conclusions of the study emphasize the importance of continuing linguistic landscape research in the context of globalization and digitalization of public space. A deep understanding of the interrelationships between language, society and culture in the context of intensive interaction of various linguistic communities in the common information and cultural space is extremely necessary at the present stage. The study of the linguistic landscape will make it possible to form effective strategies aimed at developing language policy, improving intercultural communication and preserving linguistic diversity. Key words: linguistics, landscape, Scopus, linguistic diversity, scientific publications.